The Confessional Differences in Perception of the Factors Insulting the Religious Feelings - Politova, Svetlana Pavlovna; Silaeva, Zoya Vladimirovna (International Journal of Criminology and Sociology, 2022)
The current study is concerned with the actual for modern Russia problem of law enforcement practice under Article 148 of the Criminal Code, which provides for liability for actions committed with the purpose of offending religious feelings. At the same time, until now, there is no uniform understanding of what the religious sentiments of believers are and what are the actions that can insult them. The article describes the results from the survey organized to study confessional differences in the perception of factors of offending the feelings of the believers. The study involved 220 representatives of the main confessions of Russia: Christianity, Islam, Judaism and Buddhism. The respondents were asked to choose those actions from the proposed list that could wound their religious feelings or to suggest their own variant (all questions were composed with reference to doctrinal characteristics of confessions, but were of similar nature). The results obtained indicate that insult to the feelings of believers is subjective and has confessional characteristics determined by the content of the religious teachings. The results of the study are of unconditional novelty and significance in view of great social demand and lack of similar studies.